2017
DOI: 10.9734/ijpss/2017/32859
|View full text |Cite
|
Sign up to set email alerts
|

Content of Cd, Cr and Pb in Soil and Amaranthus caudatus Grown in Yamaltu-Deba Local Government Area, Gombe State, Nigeria

Abstract: The concentrations of some heavy metals (Cd, Cr and Pb) were determined in top soil and (Amaranthus caudatus) samples from irrigated farmlands in Yamaltu, Gombe State, Nigeria, using Atomic Absorption Spectrophotometer (AAS). The results show that the heavy metals contents were higher in the soil than in the amaranths. The results also revealed the trend in soil metals concentration as Cd > Pb > Cr and for the plant as Cd > Cr > Pb. Transfer factors (TF) decreased in the following order: Cd > Pb > Cr respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…The OM depletion might be due to crop uptake exacerbated by continuous cropping without adequate measures for nutrient replacement either through the use of inorganic fertilizer or other forms of soil conservation measures. Degradation and low humus content in savanna soils have been reported by several researchers (Raji et al, 1995;Odunze, 1998;Ibrahim et al, 2010;Ibrahim and Umar, 2012;Maniyunda, 2012). However, the loss rate of humus is noted to be higher in cultivated soils than Fadama, forest and mining land soils.…”
Section: Biological Degradationmentioning
confidence: 72%
“…The OM depletion might be due to crop uptake exacerbated by continuous cropping without adequate measures for nutrient replacement either through the use of inorganic fertilizer or other forms of soil conservation measures. Degradation and low humus content in savanna soils have been reported by several researchers (Raji et al, 1995;Odunze, 1998;Ibrahim et al, 2010;Ibrahim and Umar, 2012;Maniyunda, 2012). However, the loss rate of humus is noted to be higher in cultivated soils than Fadama, forest and mining land soils.…”
Section: Biological Degradationmentioning
confidence: 72%
“…Some farmers collect the decomposed portions of these wastes and apply to their farmlands as manure so as to improve soil fertility and increase crop yields without proper knowledge on the chemical composition and the risks associated with such practices. Several literatures have reported that MSW from urban areas are applied as manure on agricultural lands to enrich nutrient depleted soils that have been under cultivation for many years and are deficient in essential nutrients needed for crop growth, thus becoming a cheaper alternative source of nutrients for the farmers (Ogunyemi et al, 2003;Amusan et al, 2005;Okoronkwo et al, 2005;Adajia et al, 2008;Ebong et al, 2007;Ibrahim and Salem, 2017). The MSW improve both soil physicochemical properties and nutrient status for better crop production.…”
Section: Introductionmentioning
confidence: 99%